HUBUNGAN PERILAKU KESEHATAN TERHADAP RISIKO PENYAKIT BERBASIS LINGKUNGAN PADA MAHASISWA DI WILAYAH ASRAMA RUSUNAWA UNTAN PONTIANAK - Afriani, Feni (School of Nursing, Faculty of Medicine, Tanjungpura University, 2021)
Background: In terms of the health behavior of students in the Tanjungpura University Dormitory area, it was found that the majority of students did light activities such as frequently using eating and drinking utensils at the same time, sanitation every 2/3 weeks, inappropriate disposal of waste water and untidy rooms arrangement with humidity and dry room temperature which might cause itching/redness of the skin, fever, flu and cough. The behavior patterns and habits that the researcher found did not meet health standards which could lead to diseases if they did not maintain the cleanliness of the environment in the area. Methods: This research was descriptive quantitative data study with cross sectional design which was conducted from May to August 2020 using 2 questionnaire instruments Likert and Guttman scale. The research sample consisted of 104 student respondents. Results: There was a relationship between health behavior and the risk of environmental-based diseases in the area of Tanjungpura University Dormitory Pontianak with a statistical test result p value of 0.000 where the majority of respondents were 20-22 years old and a year length of stay. Respondents lived on the 1st floor and the average number of residents in 1 room was 4 people. Conclusion: Health behavior had a strong influence on health status, daily eating and drinking habits which did not meet health standards and led to diseases.